Cluster Headache in Childhood: Case Series From a Pediatric Headache Center. (January 2014) - Mariani, Rosanna; Capuano, Alessandro; Torriero, Roberto; Tarantino, Samuela; Properzi, Enrico; Vigevano, Federico; Valeriani, Massimiliano
Childhood-onset cluster headache is an excruciatingly painful and distressing condition. A retrospective study was conducted on charts of patients referring to our Headache Center. Those diagnosed as cluster headache were selected. We identified 11 children (6 males and 5 females). The mean age of cluster headache onset was 10 years (range: 5-16). All children had episodic cluster headache. All children had unilateral orbital pain; 7 patients had throbbing pain, whereas 4 children complained stabbing pain. The mean duration of the attack was 86 minutes (ranging from 30 to 180 minutes). The frequency of episodes was between 1 and 4 per day. All children had the typical cluster headache autonomic features, such as lacrimation, conjunctival injection, ptosis, and nostril rhinorrhea. Steroids showed a good clinical efficacy in interrupting cluster headache recurrence. As symptomatic drugs, acetaminophen as well as ibuprofen were ineffective; indomethacin was effective in 1 case.